Effect of sucrose on the fatty acid metabolism of adventitious root cultures in vitro of Stevia rebaudiana - Follador, Bruna Gabrieli (2021)
In this study, the effect of sucrose on the neutral lipid profile of adventitious root cultures of Stevia rebaudiana was evaluated. The cultures were obtained employing a roller bottle system. In this system, Schott-type flasks were used, which contained Murashige and Skoog liquid medium at 33.3% strength (MS/3) supplemented with 30, 60, and 80 g L-1 of sucrose, respectively, and 10.7 mM 1-naphthaleneacetic acid (NAA). The spectroscopic analyzes showed that the portion of polyunsaturated fatty acids (PUFAs) was highest in roots treated with 30 g L-1 of sucrose. The spectrometric analyzes showed that the palmitic acid was found to be present in relatively higher amounts in the roots submitted to the MS/3-30 g L-1 (31.9%) and MS/3-60 g L-1 (29.5%) sucrose treatments, and lower in the treatment with MS/3-80 g L-1 (28.8%) of sucrose. Also, the treatment using 30 g L-1 of sucrose was the best for obtaining unsaturated fatty acids (UFAs) in the culture, with a relative percentage of 62.9%. Our results indicate that the MS medium that received 30 g L-1 of sucrose induced a lesser abiotic stress condition, which favored PUFAs production in the adventitious root cultures of S. rebaudiana.